2022
DOI: 10.1109/oajpe.2022.3155973
|View full text |Cite
|
Sign up to set email alerts
|

Load-Altering Attacks Against Power Grids Under COVID-19 Low-Inertia Conditions

Abstract: The COVID-19 pandemic has impacted our society by forcing shutdowns and shifting the way people interacted worldwide. In relation to the impacts on the electric grid, it created a significant decrease in energy demands across the globe. Recent studies have shown that the low demand conditions caused by COVID-19 lockdowns combined with large renewable generation have resulted in extremely low-inertia grid conditions. In this work, we examine how an attacker could exploit these scenarios to cause unsafe grid ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…As a cyber-physical system, the power grid, including distribution systems, is vulnerable to various forms of cyberattacks [2]- [3] such as false data injection attacks [4] and load altering attacks [5]. These attacks are threats to the stability and control of the target power grid.…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…As a cyber-physical system, the power grid, including distribution systems, is vulnerable to various forms of cyberattacks [2]- [3] such as false data injection attacks [4] and load altering attacks [5]. These attacks are threats to the stability and control of the target power grid.…”
Section: A Related Workmentioning
confidence: 99%
“…Constraint (5) and the remaining constraints form the inner level optimization problem that characterize what the attacker believes will be the response of the operator to their attack. Constraint (5) maximizes the load served.…”
Section: B Attack Objective Modelmentioning
confidence: 99%
“…The IoT is a network of connected devices including smart appliances (e.g., smart thermostats, air-conditioning, heat pumps, EVCS points, etc. ), enabling the exchange of information between devices and users leveraging wired and wireless connections [80]- [82]. These IoT-enabled devices are connected to the load-end of DERs and their operation is typically orchestrated remotely by their end users.…”
Section: B Der Device Levelmentioning
confidence: 99%
“…Researchers have demonstrated that attackers can manipulate IoT-connected devices in low-inertia EPS (e.g., relying on renewable generation) and other exogenous conditions to cause unsafe grid operation. That is, in [82], [84], the authors investigate the impact on grid stability of load altering attacks -if multiple IoT-connected high-wattage devices are compromised simultaneously -during the COVID-19 lockdown period. This adversarial behavior is enabled by the absence of overarching defense mechanisms, such as anti-viruses, and the sporadic provision of software/firmware updates and security patches which further weaken the device security posture.…”
Section: B Der Device Levelmentioning
confidence: 99%
“…Thus, adversaries can compromise local controllers and sensors to create voltage and frequency instabilities. Additionally, manipulation of load sharing patterns among different power generation resources within the MG can disrupt the optimal scheduling [12]. In Algorithm 1, we present the post-installation attack methodology followed by the rootkit.…”
Section: Introductionmentioning
confidence: 99%